How Do EFL University Teachers Regulate Their Negative Emotions While Teaching in the Classroom? Stories From Vietnam - Thùy, Ngô Thị Cẩm; Hương, Lê Phạm Hoài (Journal of Ecohumanism, 2024)
Research in the area of EFL teachers’ emotion regulation in the classrooms is notably underdeveloped (Li, 2023). In fact, Namaziandost et al. (2022) called for studies to find out why and how teachers make use of certain emotions in their classrooms and regulate their negative emotions that occur during their lessons. The current phenomenological study responds to these calls on the topic to explore the layers of meanings and experiences of emotions while teaching of EFL university teachers in Vietnam. Their classroom teaching was video recorded to select incidents in which their emotions were captured. They then were involved in stimulated recall interviews and writing journals for reflections and explanations why they expressed and regulated their emotions in those incidents. The findings indicate that the teachers’ unpleasant emotions were mainly evoked by students’ behaviours in the classrooms, including their discipline matters, lack of engagement in the lessons, and failure to give correct answers to the teachers’ questions. To handle emotions of irritation and disappointment, the teachers applied the strategy to adjust their attention and manipulated the reappraisal strategy to eliminate their negative emotions by immersing into an alternative teaching activity or context for refreshment. Implications from these findings are provided for EFL teachers to reduce negative emotions for better moods in teaching English.